Estrategias de aprovechamiento para los residuos de la rallandería de yuca "Pedro Pablo" del sitio Olla Vieja - Cedeño Cedeño, Ronny Sleyder (2023)
This research was carried out in Pedro Pablo cassava mill in "Olla Vieja" site belonging to Canuto parish in Chone canton, with the objective of using the cassava residues (bagasse, peel and residual water) with the purpose of searching for strategies of utilization. For the diagnosis of the current situation of the Pedro Pablo cassava shredder, quantitative and qualitative methods were applied, as well as direct observation, georeferencing, descriptive statistical analysis, documentary and interview techniques. The cassava residues were characterized by physicochemical analysis, gravimetry, as well as methods such as Kurschner and Hoffer and the starch test (Iodine test). Subsequently, the plasticity of the cassava residues and the utilization review were determined through documentary analysis. The results show that the shredder processes a total of 2500 kg/day of raw material (cassava) and a production of 808 kg/day of starch, being the cassava species known as "Colombian" the most used. The cassava residues were characterized and the results were for bagasse: (humidity: 11.45%, ash: 1.95%, pH: 4.58, cellulose: 2.08%, starch: yes); peel (humidity: 10.67%, ash: 1.95%, pH: 4.58, cellulose: 2.08%, starch: yes); husk (humidity: 10.67%, Ash: 7.89%, pH: 5.43, cellulose: 44.18%, starch: yes); residual water (moisture: 99.76%, Ash:0.036 %, pH:6.37, cellulose: 0.74%, starch: yes). The plasticity of bagasse was higher than that of cassava peel. Finally, through documentary analysis, strategies for the use of waste were found, demonstrating that animal feed and bioplastics.